2019
DOI: 10.1002/ccd.28419
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of hybrid vascular closure technique using both a suture‐ and collagen‐mediated closure device after transfemoral transcatheter aortic valve implantation

Abstract: Objectives: To evaluate the clinical utility and feasibility of a hybrid technique for obtaining vascular hemostasis by combining a suture-and a collagen-mediated system after transfemoral transcatheter aortic valve implantation (TF TAVI) in a real-world setting.Methods: In 75 consecutive TF TAVI procedures, we investigated a hybrid closing method to achieve hemostasis at the large bore puncture site using a combination of one presuture closure system (ProGlide) and one collagen-mediated system (Angio-Seal). V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, it has been suggested that a hybrid strategy combining suture and plug vascular closure devices may have greater efficacy and a lower risk of subsequent peripheral ischemia after TAVI than double suture devices ( 9 , 22 ). Gmeiner ( 17 ) et al demonstrated that this strategy reduces arterial wall constriction and tension while retaining the benefits of both devices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that a hybrid strategy combining suture and plug vascular closure devices may have greater efficacy and a lower risk of subsequent peripheral ischemia after TAVI than double suture devices ( 9 , 22 ). Gmeiner ( 17 ) et al demonstrated that this strategy reduces arterial wall constriction and tension while retaining the benefits of both devices.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, bleeding risk decreased during the past years due to evolution of closure devices and TAVI delivery catheters. [34][35][36] Additionally, intraprocedural ACT-guided UFH administration reduced risk for bleeding as well. 9 Moreover, anticoagulation is more effective in preventing leaflet thrombosis in comparison to antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Ani et al 1 report a series of 75 patients who underwent percutaneous closure of the femoral arteriotomy using a “hybrid” closure technique. Much of the vascular access and closure approach in transcatheter aortic valve replacement (TAVR), and indeed so much of the overall procedure itself, is in a state of constant evolution that the entire procedure could be considered a hybrid of devices and methods.…”
mentioning
confidence: 99%